Transforming Family Welfare Education Management through the Utilization of Information Technology in the Digital Era - Tambingon, Henny (International Journal of Information Technology and Education, 2025)
This article examines how the use of information technology is reshaping the management of the Family Welfare Education Department at a university within the context of digital transformation. The research focuses on changes in managerial processes, academic governance, learning services, and operational support triggered by the adoption of digital systems. This study uses qualitative methods through in-depth interviews with department heads, lecturers, and educational staff, as well as analysis of relevant policy documents and managerial practices. The findings indicate that information technology integration improves decision-making speed, administrative transparency, and the effectiveness of internal coordination. Digital learning platforms expand flexibility and enhance the quality of pedagogical interactions, while integrated academic management systems improve data accuracy and service quality. However, this study also identifies challenges such as varying human resource readiness, the need to strengthen digital literacy, and dependence on unstable infrastructure. Theoretical implications confirm that digital transformation in vocational education requires structural changes, an adaptive work culture, and continuous investment in technology. Practically, the research findings provide strategic recommendations for universities in formulating more systematic, inclusive, and quality-oriented digital transformation policies.